Dynamics Rural Community Social - Birrulwalidain, Muh. Fikron Birrulwalidain (Lembaga Bale Literasi, 2024)
Journal This discuss about dynamics social events that occur among people public rural. With focuses on interaction social, values culture , and changes in structure social , research This describe development public rural in face ongoing challenges of the times changed . Research methods involve surveys, interviews, and observations participative For get comprehensive understanding _ about dynamics social the. Study This highlighting influencing factors _ change social in rural areas, incl globalization, modernization, and migration resident. Findings study identify exists change values traditional, shift in structure family, and impact technology information on the pattern communication public rural. Apart from that, analysis also includes involvement public in activity social, policy development, and empowerment local. Research result This give contribute to understanding We about adaptation public rural to change social and how they guard identity culture they in face current globalization. Implications policies are also discussed For support development sustainability and prosperity public rural. Journal This give outlook important for researchers, academics , and makers interested policy _ in understand dynamics social public rural in context changing times.